Effect of yoga on general health: food habits versus blood groups - Balkrishna, Acharya; Verma, Anita; Bhattarai, Rachana; Gowda, G. Paran (International Journal Of Community Medicine And Public Health, 2017)
Background: In this paper, we attempted to critically analyze the relation between food habits intake versus different blood groups. In majority of the cases we found that there is a close link between the food habits versus the blood groups. Methods: As a sample measure, we collected 50 sample blood groups and their respective food habits. Descriptive statistics is applied to know the average number of people having different food habits versus blood groups. The study covers 25 females and 25 males. The target groups cover students, public and staff of Patanjali Yogpeeth and also patients. Results: The findings of the study show that the 4 major blood groups A, B, AB and O have almost the same food habits in terms of calorie intake. Secondly, the study shows that there is a probability of blood groups having a relation to different ailments which could be treated with appropriate dieting systems and energy. Thirdly, the sample study shows that people having AB blood group may be more prone to mental discomforts for which Aloevera juice along with general yoga practices has been suggested followed by other blood groups; A, B and O. Conclusions: This study will be useful for all the medical and paramedical practitioners, dieticians, nutrition experts. It will have general health policy implications at primary and sub center level centers.